Usefulness of 99mTc-HMDP scintigraphy for the etiologic diagnosis and prognosis of cardiac amyloidosis. (2nd October 2015) - Galat, Arnault; Rosso, Jean; Guellich, Aziz; Van Der Gucht, Axel; Rappeneau, Stephane; Bodez, Diane; Guendouz, Soulef; Tissot, Claire-Marie; Hittinger, Luc; Dubois-Randé, Jean-Luc; Plante-Bordeneuve, Violaine; Itti, Emmanuel; et al.
Abstract: Background : Amyloidosis is characterized by extracellular deposits of insoluble proteins that cause tissue damage. The three main types are monoclonal light chain (AL), wild-type transthyretin (wt-TTR) and mutated transthyretin (m-TTR) amyloidosis. Cardiac amyloidosis (CA) raises diagnostic challenges. Objective : To assess the diagnostic accuracy of 99m Tc-HMDP-scintigraphy for typing CA, differentiating CA from non-amyloid left ventricle hypertrophy (LVH), and predicting outcomes. Methods : 121 patients with suspected CA underwent 99m Tc-HMDP-scintigraphy in addition to standard investigations. Results : CA was diagnosed in all AL ( n  = 14) and wt-TTR ( n  = 21). Among m-TTR ( n  = 34), 26 had CA, 4 neuropathy without CA and 4 were asymptomatic carriers. Of the 52 patients with non-amyloid heart disease, 37 had LVH and served as controls. 99m Tc-HMDP cardiac uptake occurred in all wt-TTR, in m-TTR with CA except two and in one AL. A visual score ≥ 2 was 100% specific for diagnosing TTR-CA. Among TTR-CA, heart-to-skull retention (HR/SR) correlated with CA severity (LVEF and NT-proBNP). Median follow-up was 111 days (50;343). In a multivariate Cox model including clinical, echocardiographic and scintigraphic variables, NYHA III-IV and HR/SR > 1.94 predicted acute heart failure and/or death. Conclusions : This preliminary study suggests that 99m Tc-HMDP-scintigraphy may aid differentiation between transthyretin and AL-CA as well as CA from other LVHs. 99m Tc-HMDP-scintigraphy appears to provide prognostic information in CA.